Answer:
D im pretty sure :) hope this helps
Step-by-step explanation:
Answer:
The answer is B) b
Step-by-step explanation:
According to the Trapezoid area formula, the area of the trapezoid is [(2d+a+b) × c] ÷ 2, however the area also equals (d+b) × c.
So d+(a+b)/2=d+b
(a+b)/2=b
a+b=2b
a=b
hope this helps <3
Answer:
Solving the system of equations:
x: 1
y: 2
Step-by-step explanation:
Plug it in to see if it is right, to make sure of course. Better to be safe than sorry.
Answer: C
Step-by-step explanation: all real numbers can solve this problem
<h3>(-3j²k³)²(2j²k)³</h3>
(-3j²k³)²(2j²k)³ = <em>When a power is raised to a power the exponents have to be multiplied.</em>
= (-3²j⁽²*²⁾k⁽³*²⁾)(2³j⁽²*³⁾k³) = <em>We can take out the constants</em>
= (9)(8)(j⁴k⁶)(j⁶k³) = <em>We can group the same variables</em>
= 72(j⁴j⁶)(k⁶k³) = <em>When multiplying two powers that have the same base, you have to add the exponents.</em>
= 72 j⁽⁴⁺⁶⁾k⁽⁶⁺³⁾ = 72j¹⁰k⁹
Answer = 72j¹⁰k⁹
Hope this helps!